Prevalence and risks of hepatitis E virus infection in blood donors from the Western Cape, South Africa. Issue 8 (29th June 2020) - Maponga, Tongai G.; Lopes, Tatum; Cable, Russell; Pistorius, Charlotte; Preiser, Wolfgang; Andersson, Monique I.
Abstract : Background: Transfusion‐transmitted hepatitis E virus (HEV) infection is a potential risk to recipients of blood transfusions. Infection with HEV poses a high risk to immunocompromised recipients with an increased likelihood of developing chronic infection. The aims of this study were to determine the prevalence of past and active HEV infections in donors from the Western Cape and to identify the risk factors associated with infection. Materials and methods: We prospectively tested 10 250 blood donors for HEV infection. A risk factor sub‐study investigated 250 donors who completed a questionnaire, and plasma samples were tested for HEV IgG antibodies and pooled for HEV RNA detection. The demographic and risk factors associated with HEV infection were assessed. The molecular study tested 10 000 individual donations using a commercial assay to detect viraemia. HEV viral load and genotype were also determined. Results: The overall anti‐HEV IgG seroprevalence was 42·8% (107/250) among donors participating in the risk factor sub‐study. The likelihood of past HEV infection was higher with an increase in age. Of the 10 000 donor samples individually tested for HEV RNA, one sample was positive with a viral load of 7·9 x 10 4 IU/ml and belonged to HEV genotype 3. Conclusion: We found a high seroprevalence of anti‐HEV IgG but a low HEV RNA prevalence among donors in the Western Cape, South Africa. The study provides evidence for a potential risk of HEV contamination in the blood supply in South Africa. A cost–benefit analysis is needed before considering the introduction of routine donor screening in our setting.